Analisis Penerapan QCC Pada Proses Drying Untuk Meminimalkan Cacat Produk Di Plant Spray Dryer Pada PT XYZ - Wawan, Wawan; Prasetyo, Rian; Komariah, Ainur (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
PT. XYZ is a company operating in the international standard Agro chemical industry. Products produced by PT. XYZ is ethanol, SCP30 and humic compounds. The aim of this research is to analyze SCP30 product defects, determine the factors that cause defects, and analyze how production control is implemented. The research used the QCC method and the research itself was carried out at PT. XYZ which is located in Kebakkramat. The author carried out research by observing the production process time and conducting direct interviews in order to find out and conclude the causes of product defects. Based on findings in the field, there are 3 types of defects, namely less dry, soft and burnt defects. After carrying out analysis, observation and interviews with related parties, it can be concluded that the causes of product defects occur. then we can propose improvements using the 5W+1H analysis. After improvements and implementation of QCC, it was found that the defect reduction was 7.11%, although it was still above the company standard, namely 6%. The decrease in soft and less dry defects reached zero defects while burnt defects increased. However, it is not a problem for the company because it can still be used compared to other defects. Next, standardization is made. This research can still be continued until it reaches zero defect